Surface hydrophobics mediate functional dimerization of CYP121A1 of Mycobacterium tuberculosis - Amit Kumar (Nature Portfolio, 2021)
Abstract Tuberculosis is caused by the pathogenic bacterium Mycobacterium tuberculosis (Mtb) and remains the leading cause of death by infection world-wide. The Mtb genome encodes a disproportionate number of twenty cytochrome P450 enzymes, of which the essential enzyme cytochrome P450 121A1 (CYP121A1) remains a target of drug design efforts. CYP121A1 mediates a phenol coupling reaction of the tyrosine dipeptide cyclo-L-Tyr-L-Tyr (cYY). In this work, a structure and function investigation of dimerization was performed as an overlooked feature of CYP121A1 function. This investigation showed that CYP121A1 dimers form via intermolecular contacts on the distal surface and are mediated by a network of solvent-exposed hydrophobic residues. Disruption of CYP121A1 dimers by site-directed mutagenesis leads to a partial loss of specificity for cYY, resulting in an approximate 75% decrease in catalysis. 19F labeling and nuclear magnetic resonance of the enzyme FG-loop was also combined with protein docking to develop a working model of a functional CYP121A1 dimer. The results obtained suggest that participation of a homodimer interface in substrate selectivity represents a novel paradigm of substrate binding in CYPs, while also providing important mechanistic insight regarding a relevant drug target in the development of novel anti-tuberculosis agents.